Human naïve B cells show evidence of anergy and clonal redemption following vaccination - Brian L. P. Dizon; Prasida Holla; Evan C. Mutic; Paul Schaughency; Susan K. Pierce (npj Vaccines)
Abstract In an era of predicted emerging pandemics, the production of effective vaccines may require an in-depth understanding of the biology of human naive B (BN) cells. Here we provide evidence that the majority of BN cells expressed CD73, an ecto-5’-nucleotidase often associated with immune cell suppression, and demonstrated features of anergy, including an IgMlowIgD+ surface phenotype, reduced calcium flux in response to IgM crosslinking, and increased PTEN expression. Analysis of antibody sequences encoded by the inherently autoreactive VH4-34 heavy chain produced by plasmablasts seven days following influenza vaccination showed that in younger but not in older individuals, anergic BN cells provided a reservoir of B cells capable of responding to vaccination by somatic mutation, resulting in diversification and loss of autoreactivity. These results suggest that effective human vaccines may require the ability to awaken or ‘redeem’ anergic BN cells that can be repurposed to participate in pathogen-specific responses.